SUTD and SMU jointly launch inaugural undergraduate dual degree programme in technology, design and management - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
This May, the Singapore University of Technology and Design (SUTD) and the Singapore Management University (SMU) will admit the first batch of dual degree undergraduate students. Up to 45 top achievers will have the unprecedented opportunity to pursue an engineering degree from SUTD and a business management degree from SMU concurrently. The four-year programme, aimed at producing graduates who will be highly effective in an increasingly complex globalised world, will prepare students to be technology and management-grounded leaders, innovators, and entrepreneurs. Students will spend time at both campuses, and will take SUTD and SMU courses from the first academic year, thus benefitting from a uniquely integrated and interdisciplinary learning experience over four years of study. The programme will also include up to six courses to be co-developed by SMU and SUTD. To attract top Singaporean students to the programme, scholarships offered to deserving students will cover full tuition fees, including allowances for overseas internship, community service, and more. Students in this programme will graduate with a Bachelor of Business Management from SMU and a Bachelor of Engineering from SUTD with a specialisation in one of the three engineering pillars: Engineering Product Development Systems and Design or Information Systems Technology and Design.